Design of the Process of Obtaining Fresh Cheese in the Province of Chimborazo in the Superpro Designer Software - Vinocunga Pillajo, Reni Danilo (2023)
Fresh cheese is a food rich in nutrients, it is also considered an excellent food supplement. In Ecuador, cheese production is carried out in an artisanal way, which implies insufficient hygienic-sanitary conditions and commercial quality. The objective of this work was to simulate the process of obtaining fresh cheese using the commercial simulator SuperPro Designer. The methodology used consists of sequential stages. Four capacities of 500 L, 2,000 L, 3,500 L and 5,000 L were established. The technology selected for obtaining fresh cheese consisted of several processes and unit operations: standardization, heating, pasteurization, mixing, coagulation, cutting of the curd, draining, pressing, addition of salt and packaging of the cheese. The economic indicators showed as the best alternatives the capacities of 2,000 L, 3,500 L and 5,000 L, with the recovery period of these three capacities being less than 2.18 years.